Generating meaningful and easy-to-interpret sustainability data to support decision making: a method and a case study - Vanderkooy, Matt; McMaster, Michaye; Wealthall, Gary; Vidumsky, John (Águas Subterrâneas, 2013)
Recently many corporations, organizations, and governmental agencies are putting a greater emphasis on evaluating sustainability of projects and products to help guide implementation and production. This paper and presentation presents a method to generate and present sustainability data from Life Cycle Assessments (LCAs) that are meaningful, easy-to-interpret and simplify decision making. Three key outputs of the method include (1) a sustainability ranking table that can easily be incorporated into decision making frameworks, (2) a sustainability probability distribution to examine uncertainty, and (3) a contribution network to analyze and optimize sustainability. This paper and presentation showcases the method by applying it to evaluate the sustainability of remedial options for a coal tar contaminated site.